P244 The impact of "Seven Day working" on Respiratory inpatient activity at St Helens and Knowsley NHS trust. – "The slow drift model". (12th November 2015) - Twite, S; Stockton, P; Sreeguru Lakshman, V; Malhotra, P; Alapati, S; Koduri, S; Naveed, J; Howard, J
Abstract : St Helens and Knowsley NHS trust (STHK) have re designed the acute pathway for medical admissions. Investment in Consultant numbers has allowed the Acute Medical Admissions (MAU) team and the speciality teams to provide robust Consultant input to their areas Monday to Sunday. Speciality Consultants have been released from the acute medical take and traditional Physician of the day (POD) activities. Advantages of a Consultant led seven day service include: Greater parity of service across seven days a week; high level of clinical competence ensuring rapid and appropriate decision making; improved outcomes for patients; skilled judgement and performance leading to the most effective working and more efficient use of resources; and GP access to the opinion of a fully trained doctor. Respiratory Consultant numbers have increased from 5 to 8 (7.5 WTE). 90 PA's have been invested in the service. The inpatient service is resourced with 64 inpatient beds. General principles have been applied to the inpatient service. These include: Each Consultant provides daily review, in the form of 3 ward rounds and 2 board rounds, to their allocated patients; rounds are performed in the first half of the day to aid patient flows and discharges; Consultants provide cross cover during leave; and weekends are covered on a 1 in 8 basis. Alteration to outpatient and elective services has also occurred. Results: 160% increase in weekend Respiratory discharges and 48% increase in overall Respiratory discharges, with no increase in bed base. Significant fall in Respiratory length of stay. 50% improvement in MET calls per discharge reflecting improved quality of care. Significant fall in readmissions. Positive feedback from patients, relatives and staff. Additional benefits include improved elective and outpatient productivity due to less clinic cancellations enforced by the traditional POD model of acute medical activity. Outpatient activity has increased by 50% and elective (Bronchoscopy) activity by 35%. Improved junior doctor support and education are also achieved. Significant decrease in departmental complaints. Discussion: The "slow drift" model presented here offers significant advantages over traditional working practices for both efficiency and outcome. The return on investment contributes to cost improvement programs.